Decision Support System for Selecting Tourism Object in Surabaya City Using Simple Additive Weighting Based on Android - Putri Agustin Merditawati; M Mahaputra Hidayat; Rahmawati Febrifyaning Tias (Fakultas Teknik Universitas Bhayangkara, 2018)
In this final project will discuss the implementation of the Decision Support System Attractions in Surabaya usingSimple Additive weighting. Issues to be taken is to obtain the best results of 50 attractions in Surabaya based on thelocation of the user to take advantage of the Android-based operating system, to make it more easier for users toaccess these applications. To obtain the value of the distance criterion, the application is using the formulaHaversine. The results of the election decision support system application attractions in Surabaya using SimpleAdditive weighting method is the obtainment of the highest values of attractions based on user location with weightsto each criterion especially distance criterion which has a weight of 0.3.